Design of 3‐aminophenol‐grafted polymer‐modified zinc sulphide nanoparticles as drug delivery system - Milad Abniki; Zahra Azizi; Homayon Ahmad Panahi (IET Nanobiotechnology)
Abstract Zinc sulphide (ZnS) nanoparticles were synthesized by the coprecipitation method. The ZnS nanoparticle surface was polymerized with allyl glycidyl ether (AGE), and 3‐aminophenol was then deposited as a ligand on nanosorbent. The modified nanosorbent was investigated with Fourier transform infrared spectroscopy and thermogravimetric analysis. The particle size of the modified nanosorbent was studied with scanning electron microscopy. Some characteristic factors of the adsorption process such as pH and time were investigated for famotidine using the modified nanosorbent. The equilibrium adsorption study of famotidine by 3‐aminophenol‐grafted AGE/ZnS was analysed by adsorption isotherms of the Langmuir, Freundlich, and Temkin models. The famotidine‐releasing process was investigated in simulated biological fluids (intestinal fluid at pH of 7.4 and gastric fluid at pH of 1.2) and demonstrated 65% and 73% famotidine release during periods of 30 h (pH = 7.4) and 60 min (pH = 1.2), respectively. These results reveal the optimal performance of 3‐aminophenol‐grafted AGE/ZnS for sustained drug delivery.